2003
DOI: 10.1097/00129689-200310000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Talc Pleurodesis for Recurrent, Symptomatic Pleural Effusion Following Cardiac Operations

Abstract: Seventeen patients who underwent a cardiac operation developed a recurrent, symptomatic pleural effusion ultimately requiring video-assisted thoracic surgery (VATS) and talc pleurodesis. These patients represented 0.4% of all patients undergoing a cardiac operation over the same time period. Compared with an age- and sex-matched control group of cardiac surgery patients, patients requiring VATS for recurrent pleural effusion were more obese with higher body mass index (31.9 +/- 1.2 versus 28.3 +/- 1.4 kg/M2, P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
0
9
0
1
Order By: Relevance
“…One patient was still receiving periodic thoracentesis 12 months post-CABG. Paull et al (7) found 17/4,272 (0.4%) patients having PE after cardiac surgery refractory to thoracentesis. All but one of these were successfully treated with VATS pleurodesis.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…One patient was still receiving periodic thoracentesis 12 months post-CABG. Paull et al (7) found 17/4,272 (0.4%) patients having PE after cardiac surgery refractory to thoracentesis. All but one of these were successfully treated with VATS pleurodesis.…”
Section: Resultsmentioning
confidence: 99%
“…All studies but one (8) do not include follow-up, making difficult to define the effectiveness of thoracentesis or chest drainage to resolve PE, as it remains unknown in how many patients an effusion recurs. No case of recurrence was found after a VATS procedure; VATS was a safe procedure with a morbidity of 17% and no mortality (5,7,9). In patients for whom there was a significant delay before proceeding to VATS, it was not unusual to discover a trapped lung (5,7,9) that required in three cases a thoracotomy decortication (2,5,7).…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations